Solubility Enhancement of Poorly Water Soluble Drug by Using β Cyclodextrin - S, Sathvik; S, Nagaraja T.; R, Yogananda; Snehalatha; N, Chethan Patel D. (Journal of Biomedical and Pharmaceutical Research, 2022)
Aceclofenac complex is prepared by kneading method of inclusion complexation. The aim of present work is to improve the solubility and dissolution properties of a poorly water soluble drug aceclofenac, by inclusion complexation technique. Two components namely β cyclodextrin and span 60 were used in this study,  β CD is used as complexing agent and span 60 as surfactant which helps in increasing solubility and dissolution. The prepared Aceclofenac complex is evaluated in terms of compatibility, solubility, dissolution behavior with the help of FTIR, DSC, In vitro dissolution studies. The complexation parameter of β CD had an impact on the solubility of drug. The solubility of complexes was progressively improved when compared to pure Aceclofenac drug in water. The prepared Aceclofenac complexes were subjected to dissolution study.  At the end of 60 min of dissolution study 22.32±0.42 of pure drug was dissolved. The prepared complexes showed 85.35±0.71 at 60 min. The percent of drug dissolved increased for the complexes prepared with high concentration of β CD.  The study showed that complexing property of β CD and surfactant action of span 60 has its influence on both solubility and dissolution of the prepared inclusion complexes. MDT and % DE was evaluated for the all the prepared complexes. Aceclofenac complexes prepared with high concentration of β CD showed lower MDT and higher % DE compared to pure Aceclofenac. The pure and complexed Aceclofenac were characterized by DSC studies. DSC studies showed that there was no appreciable change in the melting endotherm of prepared complexes compared to that of pure drug. The drug release from the above follows Korsemeyer-Peppas model and release mechanism was Non- Fickinian.Keywords: Aceclofenac, inclusion complex, kneading method, complexing agent, solubility, dissolution.